Anglophone presumptions in the courtrooms of Wales and the Republic of Ireland: some initial thoughts on achieving language-neutral courtrooms - Róisín Áine Costello; Catrin Fflûr Huws (Revista de Llengua i Dret - Journal of Language and Law)
In this article, we consider the legal protections afforded to Welsh in the United Kingdom, and Irish in the Republic of Ireland. We posit that existing legislation, while professing to position Welsh and Irish as variously “official” and “national” languages, in fact frames them as “other” linguistic choices, deviating from the linguistic default of English. We examine how this has occurred in both jurisdictions, in light of which we offer some initial thoughts as to how existing legislation and practice could be reframed in more linguistically neutral terms in both jurisdictions in order to prevent this “othering” of Welsh and Irish speakers.